The Influence of Peer Group Interaction and Academic Self-Concept on Academic Achievement - Cahyani, Estu Dwi; Sugiyanto (Faculty of Psychology, Universitas Surabaya, 2008)
This investigation addressed the influence of peer acceptance/rejection and academic self- concept on academic achievement. The study involved 138 students from two elementary schools in Sleman, Yogyakarta. The findings showed that there were positive and significant relationships bet- ween peer acceptance/rejection, academic self-concept, and academic achievement. Result of step- wise regression analysis showed that peer acceptance/rejection and academic self-concept influenced academic achievement (R 2 =22.7%) and peer acceptance/rejection was the main predictor of academic achievement (R 2 = 16.8%). Accepted students reached higher academic achievement than rejected stu- dents. Furthermore, reading self-concept, as a part of academic self-concept, was significantly related to Bahasa Indonesia achievement (R = 0.370, p > 0.01), general academic achievement (R = 0.337, p > 0.01), and math achievement (R = 0.276, p > 0.01). Penelitian ini melaporkan pengaruh penerimaan/penolakan sebaya dan konsep-diri akademik terhadap prestasi akademik. Studi ini melibatkan 138 siswa dua sekolah dasar di Sleman, Yogya-karta. Temuan menunjukkan adanya hubungan positif bermakna antara penerimaan/penolakan sebaya, konsep-diri akademik, dan prestasi akademik. Hasil analisis regresi bertahap menunjukkan bahwa penerimaan/penolakan sebaya dan konsep-diri akademik memengaruhi prestasi akademik (R 2 = 22.7%) dan penerimaan/penolakan sebaya merupakan prediktor utama prestasi akademik (R 2 = 16.8%). Siswa yang diterima mencapai prestasi akademik yang lebih tinggi daripada siswa yang ter- tolak. Selain itu, konsep-diri membaca, sebagai bagian konsep-diri akademik, terkait secara bermakna pada prestasi Bahasa Indonesia (R 2 = 0.370, p >0.01), prestasi akademik umum (R = 0.337, p >0.01), dan prestasi matematik (R = 0.276, p >0.01).